2013
DOI: 10.1111/ele.12109
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community responses to anthropogenically induced environmental change: towards a systems approach

Abstract: The soil environment is essential to many ecosystem services which are primarily mediated by microbial communities. Soil physical and chemical conditions are altered on local and global scales by anthropogenic activity and which threatens the provision of many soil services. Despite the importance of soil biota for ecosystem function, we have limited ability to predict and manage soil microbial community responses to change. To better understand causal relationships between microbial community structure and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
177
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(184 citation statements)
references
References 102 publications
6
177
1
Order By: Relevance
“…In contrast with other studies, examining soil and sediment-bound microbial communities (Bissett et al, 2013;Sun et al, 2013), which have observed a lack of correlations between absolute abiotic measurements and 16S rRNA OTU relative abundances, numerous correlations were observed between biotic and abiotic factors. Although consideration should be made that such approaches, wherein relative abundances are used to derive correlations between species, may overestimate the numbers of true correlations (Friedman, 2012;r14933), this analysis was effective at classifying factors characteristic of the three observed periods, namely summer, autumn and winter periods, also observed in the dbRDA analysis (Figure 2).…”
Section: Eubacterial Diversity and Compositioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with other studies, examining soil and sediment-bound microbial communities (Bissett et al, 2013;Sun et al, 2013), which have observed a lack of correlations between absolute abiotic measurements and 16S rRNA OTU relative abundances, numerous correlations were observed between biotic and abiotic factors. Although consideration should be made that such approaches, wherein relative abundances are used to derive correlations between species, may overestimate the numbers of true correlations (Friedman, 2012;r14933), this analysis was effective at classifying factors characteristic of the three observed periods, namely summer, autumn and winter periods, also observed in the dbRDA analysis (Figure 2).…”
Section: Eubacterial Diversity and Compositioncontrasting
confidence: 99%
“…Yanga Lake was selected for this study as it is has been the subject of routine monitoring, has a prior history of cyanobacterial blooms (Kobayashi et al, 2013) and, as a consequence of being fed by a single tributary (Yanga Creek), can be readily isolated from the river system, limiting the impact of inflows. In this study, we aimed to utilise a systems framework (Bissett et al, 2013) that encompasses measurement of water quality information, cell enumeration and microbial community data sets to address how abiotic and biotic factors combine and interact during cyanobacterial blooms. We performed routine monitoring over a 6-month period and performed in situ measurements, elemental analyses, cyanobacterial species identification and enumeration and 16S rRNA amplicon sequencing at five sites across the lake.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of ammonia-oxidizing microorganisms, PNR rapidly decreased after freshly adding copper and then showed a recovery tendency indicating that the changed AOA and AOB communities adapted to the subsequent stress and maintained their function. This was supported by the finding that ammonia-oxidizing microorganisms were very sensitive to and rapidly inhibited by heavy metals in the short term [44] whereas in the long-term, maintenance of ammonia oxidization-mediated ecosystem function under metal stress occurred via changes in AOB and AOA community compositions [45]. This was also confirmed by our results that PNR varied little while AOB and AOA communities highly differed between different initial copper intensities after 5 years.…”
Section: Responses Of Soil Microorganisms To a Subsequent Stresssupporting
confidence: 85%
“…Function is not phylogenetically conserved which means that one core function is being performed by various microorganisms; thus, investigation on response to disturbance based on phylogenetic structure may be misleading. This suggests that a system approach is needed, integrating community composition, process rates, temporal fluctuations, interactions, and feedbacks [45].…”
Section: Responses Of Soil Microorganisms To a Subsequent Stressmentioning
confidence: 99%
“…This pivotal process was generally presumed to be performed by ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA). AOB have been suggested to be sensitive to various soil perturbations (Bissett et al, 2013), while AOA seems to be insusceptible to environmental changes due to strongly rigid cell membranes and other cellular macromolecules (Cray et al, 2013). For example, previous studies have indicated the positive effects of organic matter on function and community of ammonia-oxidizers attributing that organic matter provides more available ammonium during degradation (He et al, 2007;Kalvelage et al, 2013).…”
Section: Introductionmentioning
confidence: 99%